Dominasi Barat dan Pengaruhnya Terhadap Dunia Islam - Ruslan, Idrus; Mawardi, Mawardi (Universitas Islam Negeri Raden Intan Lampung, 2019)
Until this moment it can be said that the West still dominates in all fields, be it economics, technology, education, agriculture, military, industry and so on. This is motivated by the arrogance of the West who wants to dominate the Islamic world (the Eastern world that is not as Western as). It cannot be denied that Western domination certainly has negative implications for the generation of Islam, but it must also be acknowledged that the advance of the West has made the Muslims flinch and realize that the Eastern world has lagged far behind them. In general there are two kinds of Muslim responses to the progress of the West, namely there are those who accept but there are also those who refuse, even though the type of Muslim accepts there are two macaas, namely those affected by secularization-westernization and Islamic modernism. Therefore the thing that must be a handle for Muslims is consistent (istiqamah) against the teachings of Islam, only by adhering to the teachings of religion, then the concern about secularization-westernization certainly does not need to happen.